Auditing the electronic accounting information system in accordance with professional auditing publications to achieve the requirements of the COBIT 2019 framework - a proposed program (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Electronic accounting systems are exposed to a group of risks, including natural risks such as fires and floods, as well as intentional risks such as data theft, viruses, or any other electronic programs that attempt in one way or another to disrupt the systems. To confront these risks, it is necessary to have programs to audit those systems. The problem of the research lies in the lack of The senior audit authorities prepare audit programs for these systems in accordance with professional audit publications, such as the information technology audit guides No. 5100, international standards, and the Information Technology Audit Guide (WIGITA) issued by INTOSAI, and taking into account what is issued by professional associations regarding frameworks for control and auditing related to information technology as a framework. COBIT 2019, which helps in achieving the goals of governance and management of the organization, The research gained importance through auditing the electronic accounting information system in accordance with the professional organizations’ issues of standards, guidelines and guides for auditing electronic systems to address the risks to which the process of transitioning from the manual to electronic accounting information system is exposed. The method of personal interviews and oral inquiries was used to identify the risks to which it is exposed. Electronic accounting information systems, The research seeks to identify the theoretical foundations for auditing the electronic accounting information system and the relevant professional publications and the COBIT 2019 framework, as well as preparing a proposed program for auditing the electronic accounting information system in accordance with the professional publications to achieve the requirements of the COBIT 2019 framework. The research concluded with a set of conclusions, the most important of which is the lack of an audit program approved by the bodies. The Supreme Supervisory and Auditing Authority and the Auditor take into account the professional publications to achieve the requirements of the COBIT 2019 framework, and the application of the proposed program helps the auditor in identifying risks and how to respond to them in terms of the nature, timing and extent of audit procedures. The research also presented a set of recommendations, most notably the need to adopt the proposed audit program to audit the electronic accounting information system and apply it in economic units, as well as the need to train regulatory authorities and inform them of countries’ experiences with regard to auditing the electronic accounting information system.